STRATEGI KOMUNIKASI PUBLIK PEMERINTAH DAERAH DI ERA DIGITAL - Khurin'In Azizah (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
The digital era has transformed local government public communication from one-way information delivery into faster, interactive, and platform-based engagement. This article aims to synthesize public communication strategies for local governments in the digital era through a literature review of relevant journals, books, and policy documents. The literature was selected using inclusion criteria related to publication period, topic relevance, and full-text availability. The findings identify eight key strategies: optimizing official social media, using integrated multichannel platforms, strengthening digital communication capacity among public officials, developing digital public information systems, maintaining conventional channels through a hybrid approach, preparing digital crisis communication protocols, expanding digital public participation, and conducting regular communication performance evaluation. These strategies are interrelated and form an integrated public communication ecosystem. Their implementation requires leadership commitment, adequate resources, cross-agency coordination, and continuous evaluation so that local governments can maintain public trust and respond effectively to digital communication challenges.